DNA barcodes and morphology reveal new species within the Cryptochironomus Kieffer from Oriental China (Diptera: Chironomidae) - Liu, Wen-Bin; Wang, Cheng-Yan; Tang, Ya-Ning; Pei, Wen-Xuan; Yan, Chun-Cai (Zootaxa, 2024)
The genus Cryptochironomus has a cosmopolitan distribution including over 140 valid described species worldwide. The morphological characteristics and DNA barcode data of Cryptochironomus inflatus Liu, sp. nov. based on specimens collected from Oriental China. DNA barcode analysis including the partial COI sequences of species of genus Cryptochironomus is conducted. An updated key to adult males of the genus is provided.